The crashworthiness of Bi-directional corrugated honeycomb aluminum under oblique loading using for nuclear spent fuel transportation casks. (April 2023) - Xing, Youdong; Yang, Siyi; Wang, Chongyang; Lu, Shiqing; Shen, Ao; Zhai, John
Highlights: In this paper, 6 kinds of Bi-directional corrugated honeycomb aluminum (BDCHA) is used to carry out compression-shear loading results with different oblique angles and installation directions by simulation (experiments are used to verify accuracy of the simulation). The deformation mode and mechanical properties are observed under different oblique angles and installation directions. Comparing with wood, the energy absorption shows the feasibility of BDCHA as a shock-absorbing filling material using for nuclear spent fuel transportation casks. Abstract: When filling materials used for nuclear spent fuel transportation casks, they will inevitably be subjected to oblique impact. The study of material performance during oblique impact is very important for their safety. In this paper, Bi-directional corrugated honeycomb aluminum (BDCHA) is used to carry out compression-shear loading results with different oblique angles (20°, 30°, 45°) and installation directions (X-FACE, Y-HOLE) by simulation (experiments are used to verify accuracy of the simulation). Quasi-static tests perform 6 kinds of materials dates with different cell thickness/cell size ratios, and observe the deformation mode and mechanical properties. The results show that the deformation of the material is mainly the torsional buckling deformation. In addition, BDCHA mainly bears the shear and compress stress. When the oblique angle and installation directions are different, the stress is different. The material of the cell thickness/cell size ratio affects the stress of the material. Finally, comparing with wood, the energy absorption shows the feasibility of BDCHA as a shock-absorbing filling material using for nuclear spent fuel transportation casks.